THE PERCEPTIONS BETWEEN JAVANESE AND MADURESE SPEAKERS TOWARDS THEIR DIALECTS IN ENGLISH CONVERSATION - Syakur, Abd.; sudrajad, wahyu; Sulistyaningsih, Sulistyaningsih; Musyarofah, Lailatul (University of Muhammadiyah Malang, 2024)
This study seeks to explore and analyze Javanese and Madurese speakers' use of their respective dialects in English conversation. In the framework of ethnically diverse Indonesian schools, certain Javanese and Madurese-speaker pupils may have trouble performing dialogue which is the reason why the researcher conducted this research. The data was online questionnaires then the result of the questionnaires was analyzed by quantitative method. The Javanese and Madurese students from three primary cities of Pasuruan, Lumajang, and Jember in East Java, Indonesia, were used as the focus of this study. At least 200 persons participated as questionnaire participants. The results of the data from online questionnaires show that the score gathered was 2118 for Javanese perception and 2576 for Madurese perception after that, 2118:3500 was 60% (neutral categorized). After the spread out of the questionnaires and measurements, the result shows both Javanese and Madurese respondents did not have a problem with their dialects each other